Gone writing : the poems of Moore on Sunday - Moore, Peter, 1956- (University of Minnesota Press, 1999)
At the end of his weekly news-in-review program, Moore on Sunday beloved WCCO-TV newsanchor Dave Moore often signed off by reciting a poem. These poems, composed by Moore's son Peter and collected here for the first time, offer a fresh and funny take on the common and not-so-common stuff of our everyday lives. Reminiscent of Ogden Nash and Tom Lehrer, with a dash of Dr. Seuss, Peter Moore's verse captures the essence of his father's wit, common sense, honesty, and warmth.